Challenges of Teaching Philosophy in the Absence of Educational Resources Among Eleventh Grade Teachers in Duhok Governorate Preparatory Schools - Ahmed, Ismael Ibrahim (Adabuna : Jurnal Pemikiran dan Pendidikan, 2026)
This study provides empirical evidence on resource-related challenges in philosophy education and informs educational decision-makers about targeted support needs for philosophy teachers. This study aimed to identify the challenges of teaching philosophy in the absence of educational resources among eleventh grade teachers in Duhok Governorate preparatory schools according to the following variables: gender, years of teaching experience, academic qualification, and school location. The study sample included 132 male and female philosophy teachers. A questionnaire consisting of 27 items was developed based on relevant literature and distributed to the research sample during November 2025. The study found statistically significant differences at the 0.05 level between the means of sample responses according to gender, years of experience, and academic qualification variables, indicating that the absence of educational resources significantly impacts teaching effectiveness differently based on these demographic factors. Significant interaction effects were also found between gender and years of experience. However, no statistically significant differences were found regarding school location. Based on these findings, the researcher recommended several measures, most importantly the need for educational authorities to provide specialized philosophy resources, establish philosophy resource centers, allocate budgets for philosophical texts and materials, and provide professional development focused on teaching philosophy with limited resources.